WJEC GCSE religious studies unit 2 religion and ethical themes - Clarke, Steve; White, Joy; Pawson, Ed (Hodder Education, 2018)
For the new Welsh specification for first teaching 2017. Trust the experts; let the market-leading publisher and subject specialists with examining experience provide accessible content that draws out the key ethical theories, helping to ensure your students have a thorough understanding - Teach the Unit 2 content confidently with comprehensive coverage of Christian, Muslim, Jewish and Buddhist beliefs and practices. - Enable students to build a strong core of knowledge with engaging activities throughout the textbook. - Boost students' confidence approaching assessment with guidance on tackling different question types. - Equip students' with the detailed knowledge they need to succeed with clear, lively explanations that make key concepts accessible to all ability levels. Covers: - Christianity: Beliefs and teachings - Islam: Beliefs and teachings - Judaism: Beliefs and teachings - Buddhism: Beliefs and teachings - Relationships - Human Rights